The Effects of Shock Vancomycin Concentrations on the Formation of Heteroresistance in Staphylococcus aureus - V. V. Gostev; Yu. V. Sopova; O. S. Kalinogorskaya; M. E. Velizhanina; I. V. Lazareva; P. S. Starkova; S. V. Sidorenko (Антибиотики и Химиотерапия, 2020)
Glycopeptides are the basis of the treatment of infections caused by MRSA (Methicillin-Resistant Staphylococcus aureus). Previously, it was demonstrated that antibiotic tolerant phenotypes are formed during selection of resistance under the influence of high concentrations of antibiotics. The present study uses a similar in vitro selection model with vancomycin. Clinical isolates of MRSA belonging to genetic lines ST8 and ST239, as well as the MSSA (ATCC29213) strain, were included in the experiment. Test isolates were incubated for five hours in a medium with a high concentration of vancomycin (50 μg/ml). Test cultures were grown on the medium without antibiotic for 18 hours after each exposure. A total of ten exposure cycles were performed. Vancomycin was characterized by bacteriostatic action; the proportion of surviving cells after exposure was 70–100%. After selection, there was a slight increase in the MIC to vancomycin (MIC 2 μg/ml), teicoplanin (MIC 1.5–3 μg/ml) and daptomycin (MIC 0.25–2 μg/ml). According to the results of PAP analysis, all strains showed an increase in the area under curve depending on the concentration of vancomycin after selection, while a heteroresistant phenotype (with PAP/AUC 0.9) was detected in three isolates. All isolates showed walK mutations (T188S, D235N, E261V, V380I, and G223D). Exposure to short-term shock concentrations of vancomycin promotes the formation of heteroresistance in both MRSA and MSSA. Formation of VISA phenotypes is possible during therapy with vancomycin.